The comparative performance in college mathematics of special science and general revised secondary curricula of MSU-IIT - Castardo-Padura, Digna Lumayag; Umila, Benwardo V.; Ganaden, Mildred S. (Quezon City College of Education, University of the Philippine Diliman, 1984)
This study compared the performance in college mathematics of the first two batches of graduates under the Special Science Curriculum (SSC) who graduated in 1982 and 1983 and those who graduated under the General Revised Secondary Curriculum (GRSC) of the Developmental High School, MSU—11igan Institute of technology during the same years.

The study attempted to investigate whether:
1. The mean performance scores in the Achievement Test in college mathematics of the Special Science Curriculum graduates differ significantly from that of the General Revised Secondary Curriculum graduates.
2. The graduates of the SSC perform better than the graduates of the GRSC in the Numerical Ability portion of the College Admission Test.
3. The SSC graduates have higher
a) average mathematics grade in college, and
b) average mathematics grade in high school than the GRSC graduates.
4. A significant relationship exists between the students' attitude toward mathematics and their performance in college mathematics.

The subjects of the study were the SSC and the GRSC graduates who enrolled in college at HSU—IIT, I ligan City during the school years 1982—83 and 1983—04. Altogether, 259 students composed the sample. Batch 81—82 had 38 students from the SSC and 80 from the GRSC while Batch 82—83 had 46 from the SSC and 95 from the GRSC.

The main instruments used were the Achievement Test and a Questionnaire—Check1ist which were both constructed by the researcher and were properly validated by competent authorities. The Achievement Test Included mathematical concepts in Freshman College Mathematics while the Questionnaire—Check1ist elicited information on student is personal background and attitudes toward mathematics.

Both instruments were administered on June 26, 1984 by the researcher, assisted by faculty and staff, mostly from the Mathematics Department of the Developmental High School (DHS).

The other data used were the high school mathematics final grades which were obtained from the Director's Office of the DHS, the mathematics grade in college from the Dean's Office, School of Science and Mathematics and the Numerical Ability portion of the College Admission Test from the Office of Admission, MSU—IIT, I ligan City.

The t—test for independent samples wag used to compare the mean g cores. The Pearson product—moment correlation technique wag used to determine the relation— ship between the student 'g attitude toward mathematics and their performance in college mathematics
The findings of the study are ag follows:
1 The SSC graduates obtained a higher mean score in the Achievement Test than those from the GRSC.
2. The SSC graduates obtained a higher
a) mean grade point average in mathematics in college, and
b) average mathematics grade in high school than their counterpart in the GRSC.
3. The SCC graduates obtained a much higher mean score in the Numerical Ability portion of the College
Admission Teat ag compared to the GRSC graduates.
5. For students from both curricula, a substantial positive relationship between the attitude toward mathematics and achievement; in college mathematics.

On the basis of the findings, the following conclusions are drawn:
1. In general, the SBC graduates are adequately prepared to tackle mathematics courses in college which accounted for their higher average grade in college mathematics as compared to the GRSC graduates.
2. Generally, the SSC graduates perform better than the GRSC graduates in the
a) Achievement Test and
b) Numerical Ability portion of the College Admission Test
3, The students' attitude toward mathematics is closely related to their performance in college mathematics. Based on the above findings and conclusions, the researcher makes the following recommendations:
1. Strengthening of the mathematics program in the high school should be maintained if not improved to the fullest.
2. The GRSC students should be also provided with opportunities parallel to those given to SSC students in terms of the mathematics courses which are to both curricula.
3. The SSC should be maintained to provide for the needs of students who would go into engineering and other science courses e Likewise, the GRSC should be also maintained to provide for vocationally inclined students.
4. Subsequent studies should be conducted to investigate whether the SSC graduates perform well in higher mathematics and science courses in college. Also, to make the researcher's comparison more complete and
extensive ono can further investigate whether the type of college program a student is enrolled in has an effect on his performance in mathematics.
Thesis [M.A.T. Secondary Mathematics] -- University of the Philippines College of Education, Diliman.
Thesis
Includes bibliographic references (310-334 leaves)
Keywords: Mathematics -- Study and teaching (Secondary) -- Philippines